Is meditation conducive to mental well-being for adolescents? An integrative review for mental health nursing - Fung Kei Cheng, PhD (Elsevier, 2016)
Childhood mental health problems not only incur a financial burden but more importantly damages individual and family well-being, which compels mental care practitioners to search for solutions, among which meditation is a more economical method. This integrative review investigates the effectiveness of meditation on psychological problems for adolescents under age of 20 through different types of meditation, though mainly mindfulness-based modes. The 36 reviewed publications include quantitative, qualitative and mixed methods research, conducted in North America, Europe, and the Asia Pacific region, related to developmental disabilities, emotional problems, and mental illnesses. Outcomes indicate a decrease in self-harm thoughts, disruptive behaviour, stress, anxiety, impulsivity, and psychological distress; and improvements in self-control, quality of sleep, emotional regulation, executive function, anger management, and social competence, resulting in better academic performance, quality of life, mental wellness, and child-parent relationships. This review suggests the integration of meditation into physical activities, and music and art therapies, as well as randomised controlled trials to examine such synthesis of these disciplines. In conclusion, meditation is a potential curative and preventive measure, both low cost and non-intrusive, for the promotion of adolescent mental wellness. This sheds light on nurses who look after children with mental health.